2018
DOI: 10.1590/0001-3765201820180456
|View full text |Cite
|
Sign up to set email alerts
|

Management of pruning and evaluation in blackberry cultivars in relation to productive characteristics and bioactive compounds

Abstract: The goal of this work was to evaluate blackberry cultivars in terms of productivity and bioactive compounds. Two experiments were conducted: in the first experiment four cultivars were evaluated (Cherokee, Guarani, BRS-Tupy and Xavante). In the second experiment, the effects of pruning management in the BRS-Tupy cultivar were evaluated with the following treatments: drastic winter pruning (zero primocane), and maintenance of two, three or four primocanes in the winter pruning. Vegetative, productive and fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The greater production due to the increase of the primocanes number is related to the increase in the number of fruits in these plants. The fact that plants with drastic pruning produced the lowest values in the productive characteristics can be due to the fact that these plants, after winter, before starting the production, need to emit shoots, unlike the other treatments where their aerial part was previously defined previous cycle (Lugaresi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The greater production due to the increase of the primocanes number is related to the increase in the number of fruits in these plants. The fact that plants with drastic pruning produced the lowest values in the productive characteristics can be due to the fact that these plants, after winter, before starting the production, need to emit shoots, unlike the other treatments where their aerial part was previously defined previous cycle (Lugaresi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In an experimental investigation of raspberries native to China, Fu et al [ 51 ] found higher levels of flavonoids in smaller fruits. Lugaresi et al [ 52 ] similarly found that blackberries with smaller fruits accumulated more flavonoids. This is similar to our findings that blackberry fruits under NO 3 − –N and CK treatments had smaller size and fruit weight.…”
Section: Discussionmentioning
confidence: 99%
“…In search of improvements and solutions to crop impediments, several authors such as Tullio & Ayub (2013), Antunes et al (2014), Marchi et al (2015), and Lugaresi et al (2018), have studied variations in the pruning system, seeking to find ideal combinations for good production and fruit quality in winter pruning. However, this study has not yet been carried out in the western region of Paraná, which presents distinct climatic conditions.…”
Section: Introductionmentioning
confidence: 99%